Religion, citizenship and migration: beyond the ‘West versus non-West’ approach (Stato, Chiese e pluralismo confessionale, 2022)
SUMMARY: 1. Religion and citizenship - 2. Religion and migration - 3. The controversial stance on religion, citizens and migrants - 4. Promoting Western values or international standards of human rights protection? - 5. Concluding remarks.ABSTRACT: In a controversy concerning the legitimacy of the wearing of the Sikh kirpan in the public space, the Italian Court of Cassation stated that immigrants have the obligation to conform their values to those of the Western world. This is but one case when a migrant’s religion has been assumed - in the public and political debate and in courts - to draw a line between what belongs to the Western civilization and what does not. This paper aims to challenge the ‘West versus non-West’ approach, by examining the interplay between religion, citizenship and migration, and by stressing that democratic countries are such only as long as they remain pluralist and accommodate diversity. Although limitations on unacceptable manifestations of religion do apply, these must pursue only legitimate aims under international standards, which do not include such a thing as the protection of Western values.